Soft Skills Assessment between Diploma and Degree Students During Industrial Training: an Industry’s Observation - Mohamad, Norizan; Nurul Hayatie Ishak, Siti; Mohamed Omar, Hasiah; Hanapi Abdul Latif, Mohd; Talmizie Amron, Mohd; Jamil, Nursuriati (International Journal of Engineering and Technology, 2018)
Industrial training program is one of the main university-industry linkages that serves the sole purpose of improving the employability of university graduates. Feedbacks from industries on graduateâ€™s performances often become a benchmark for universities to measure their graduatesâ€™ competencies. It is therefore essential to obtain industryâ€™s observation on the graduates to ensure that the universityâ€™s academic curriculums are appropriately aligned to meet industry requirements. This paper examines the observations of employers with regards to internsâ€™ soft skills at workplace. A sample of 298 respondents participated in this survey. The sample includes 40.6% (n=121) respondents for degree programmes and 59.4% (n=177) respondents for diploma programmes. A total of 28 soft skills attributes were used to examine internâ€™s performance at the organization and these attributes were classified into seven key skills competency i.e. (1) interpersonal skills, (2) communication skills, (3) intellectual skills, (4) initiative taking, (5) job attitude, (6) personal efficiency, and (7) leadership skills. The results showed that employerâ€™s observation on degree students gave higher mean scores in all of the skill categories. A t-test was executed to determine if the difference in their mean scores was significant. The result showed that there was a significant difference in the job attitude category (p value = 0.04). This directly states that degree students showed better job attitude than diploma student during industrial training in the following contexts: (1) they are more responsible to the task given, (2) they are highly motivated to complete the task given, (3) they are positive in stressful situation, (4) they are punctual and (5) they frequently come to work. Future work from this study will involve determining the possible association between job attitudes of degree students with project management skills such as in the final year project.Â Â